(untitled) (Journal of Dhaka Medical College, 2011)
Objective: To find out and asses the association between hyperuricaemia and hypertension. Methods: A case control study conducted in hypertension clinic, medicine and cardiac outpatient department of DMCH from December 2009 to November 2010 to evaluate association of hyperuricaemia and essential hypertension. A total of 51 hypertensive subjects aged 30 years and above were included as cases with same number of age & sex matched normotensive subjects as control after excluding metabolic syndrome, renal impairment, clinical evidence of liver disease, IBD, malignant diseases, vascular diseases or history of taking relevant drugs by taking detailed history and thorough physical examination and appropriate laboratory investigations. Serum uric acid was measured in all study patients. Results: The mean serum uric acid level was 5.8 ± 1.5 mg/dl vs 4.5 ± 1.2 mg/dl in case and control patients respectively. A total of 13 (25.4%) patients in cases and 5 (9.8%) patients in control had hyperuricaemia (Odds Ratio 3.15, p <0.05). So, the number of hyperuricaemic person & mean serum uric acid level were significantly higher in hypertensive Cases, as Compared to Those of Healthy Normotensive Control. Keywords: Essential hypertension; Serum Uric Acid; Hyperuricaemia DOI: http://dx.doi.org/10.3329/jdmc.v20i1.8563 J Dhaka Med Coll. 2011; 20(1) : 5-8